Herzfrequenzvariabilität (HRV) bei sportlicher Belastung - Hoos, O. (Herzfrequenzvariabilität: Gesundheitsförderung - Trainingssteuerung - Biofeedback. Internationales Symposium am 29. und 30. Oktober., 2011)
Heart rate variabitity (HRV) during exercise is dependent on exercise intensity and is influenced by a komplex and dynamic interplay of various central and peripheral modulators and control circuits. Amongst them, the arterial baroreflex, the muscle mechano- and metaboreflex, the central command, the chemoreflex, circulating catecholamines and mechanical influences of respiratory and locomotor rhythms seem to be most important. Different HRV-measures in time- and frequency-domain serve as non-invasive indicators of cardiac autonomic modulation at rest. But theses measures strongly decrease during exercise conditions and show somewhat conflicting results that do not seem to allow for a simple sympatho-vagal interpretation similar to resting conditions. While standard power spectrum analysis of HRV should be treated with caution during exercise conditions due to nonstationarity of the heart rate signal and low signal-to-noise-ratio, the use of time-variant spectral methods as well as non-linear measures of complexity and fractal scaling show much promise in this area. These alternative approaches seem to enable a differentiation of exercise intensity up to maximal exhaustion and a non-invasive estimation of ventilatory and lactate thresholds. Furthermore, recent HRV-studies during high-intensity exercise show possibilities to detect cardio-respiratory-locomotor-coupling during cyclic sports activities that should be further established in future work.